SCREENING OF CITRUS ROOTSTOCKS AND COMPARATIVE ANALYSIS OF DIFFERENT SCREENING METHOD AGAINST FOOT ROT OF KINNOW MANDARIN - UMESH KUMAR DHAKAD; SARBJEET KAUR; S. K. THIND (The Bioscan, 2014)
Phytophthora nicotianae var. parasitica is major pathogen causing foot rot/gummosis in Kinnow mandarin in Punjab conditions. Eleven rootstocks were tested against the pathogen by inoculation of spore suspension as well as leaf baiting technique. Among all rootstocks Cleopatra (45.80%) and Rough lemon (44.93%) showed maximum reduction in number of leaves, while Citrumelo (26.02%) exhibited minimum. In another parameters like seedling height, feeder root volume, feeder root length, tap root length and root weight, Citrumelo and X639 showed minimum reduction (>25%). Minimum leaf injury was observed in Citrumelo with 1.4 cm up to 120 hours and maximum for Rough lemon (2.4cm). In leaf baiting with injury, Cleopatra had maximum lesion (4 cm) at 120 hr. Comparison with number of sporangia on leaf disc not found fruitful because after 48 hours number of sporangia on leaf edge were not differed significantly. In this study Cleoapatra and Rough lemon found to be most susceptible while Citrumelo and X639 showed tolerant reaction.